THE LONG AND THE BROAD VIEW: LITERATURE IN MODERN EDUCATION - Conway, Abbott (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 1981)
Whereas tradition is recognized to be the major factor that has determined the main lines of content of our present-day curriculum, that recognition is not generally welcomed. Indeed, the word traditional in education may be said to connote a certain unquestioning if not mindless acceptance of givens. We have reached the point where it comes as a surprise to learn that when an educational system was set up long in the murky past someone had really thought about it with great care, displaying a superior reasoning and understanding that may indeed be entitled to the long survival of its product, on merit rather than on seniority. Could Alfred the Great (he of the burnt scones) have heen right: by our own standards? Conway, admitting a vested interest as an Anglo-Saxonist, cunningly presents us with a translation into modern terms of the principles and the practical benefits outlined by scholars twelve centuries ago in justification of education, and particularly of the study of language through literature. RÉSUMÉ Même si l'on admet généralement que c'est la tradition qui a déterminé les grandes lignes de nos programmes scolaires actuels, on le fait avec mauvaise grâce. En effet, le terme traditionnel en éducation dénote une certaine inconditionnalité et une acceptation presque aveugle de ce qui est acquis. Nous allons même jusqu'à nous étonner d'apprendre qu'un système d'éducation qui a vu le jour il y a bien longtemps a été élaboré avec le plus grand soin par des experts dont l'excellent raisonnement et l'intelligence expliquent en grande partie la longue survivance de leur création. Se peut-il qu'Alfred Le Grand ait eu raison; selon nos normes? Conway qui ne cache pas son intérêt pour le sujet en sa qualité d'Anglosaxoniste, nous propose avec astuce une interprétation moderne des principes et des avantages pratiques préconisés par les érudits d'il y a douze siècles pour justifier l'éducation et surtout, l'étude du langage au travers de la littérature.